Pemberdayaan Kampung Labanan Makarti dalam Prestasi Nasional - Khosiin, Khamam; Siregar, Arifin; Herly Annur, Arine; Syafiyah, Ghina (Jurnal Aksi Afirmasi, 2024)
Labanan Makarti Village, situated in Teluk Bayur subdistrict, Berau district, East Kalimantan, was established in 1984 under the Social Transmigration program, accommodating 333 families from Java and NTB as Labanan Unit III. In its early years, the village, under the leadership of its first Village Head, prioritized community structure development and the formation of agricultural groups. Fast forward to 2023, Labanan Makarti Village has received national recognition by securing the number 1 position among the best villages in Indonesia. This remarkable achievement reflects the collaborative efforts of village officials and the local community, under the leadership of village chief Mudawi. Mudawi emphasizes fair and responsible leadership based on Islamic principles, as stated in Surah An-Nisa 135 of the Quran. The village's progress is measured through eight important indicators: education, health, community participation, government, community organizations, community economics, security and appearance, together lead to the development and well-being of Labanan Makarti Village and its residents.